SILENT INTRUDER: A CASE OF INTRA CRANIAL FOREIGN BODY INSERTION AND ITS MEDICOLEGAL IMPLICATIONS (Journal of Forensic Medicine & Toxicology, 2025)
Intracranial foreign bodies (ICFBs) are uncommon and often lead to significant complications during hospital care. [...] This case highlights careful forensic evaluation before classifying injuries as grievous or simple.
Keywords: Foreign bodies; Head Injury; Penetrating; Traumatic Brain Injury; Diagnostic imaging